Comparative study between sorafenib and lenvatinib as the first‐line therapy in the sequential treatment of unresectable hepatocellular carcinoma in a real‐world setting. Issue 1 (17th December 2021) - Fukushima, Taito; Morimoto, Manabu; Ueno, Makoto; Kubota, Kousuke; Uojima, Haruki; Hidaka, Hisashi; Chuma, Makoto; Numata, Kazushi; Tsuruya, Kota; Hirose, Shunji; Kagawa, Tatehiro; Hattori, Nobuhiro; et al.
Abstract: Aims: There is a paucity of comparative data on the use of sorafenib and lenvatinib for unresectable hepatocellular carcinoma. We assessed the real‐world treatment outcomes between using sorafenib and lenvatinib for unresectable hepatocellular carcinoma in the multiple molecular‐targeted therapy era. Methods and Results: We enrolled 386 patients treated with sorafenib or lenvatinib as the first‐line therapy for unresectable hepatocellular carcinoma at multiple centers. Propensity score matching was performed to adjust for differences in baseline and tumor characteristics between the two groups. Propensity score matching identified 110 patients in each treatment group. The median overall survival was similar between lenvatinib and sorafenib (14.8 and 13.0 months, respectively; P  = 0.352). The median progression‐free survival was longer with lenvatinib than with sorafenib (7.6 and 3.9 months, respectively; P  < 0.001). The overall response rate ( P  < 0.001) and disease control rate ( P  = 0.015), as defined by the modified Response Evaluation Criteria in Solid Tumors, were significantly better with lenvatinib than with sorafenib. The median overall survival was longer in patients who received subsequent treatment than in those who did not in the sorafenib group (23.1 and 5.7 months, respectively; P  < 0.001), whereas the median overall survival with or without subsequent treatment did not differ significantly in the lenvatinib group (17.8 and 14.7 months, respectively; P  = 0.439). Conclusion: Overall survival with sorafenib and lenvatinib was not significantly different. However, patients who received subsequent treatments had longer overall survival than those who received only first‐line treatment with sorafenib, whereas lenvatinib did not show this effect. Abstract : This study compares the outcomes of sorafenib and lenvatinib for unresectable hepatocellular carcinoma using propensity score matching. Overall survival with sorafenib and lenvatinib was not significantly different. However, patients who received subsequent treatments had longer overall survival than those who received only first‐line treatment with sorafenib, whereas lenvatinib did not show this effect.